Emotion Induced Blindness Is More Sensitive to Changes in Arousal As Compared to Valence of the Emotional Distractor - Singh, Divita; Sunny, Meera M. (Frontiers in Psychology, 2017)
Emotion Induced Blindness (EIB) refers to the impairment in the identification of a neutral target image that follows a threatening or fearful distractor image. It has been suggested that valence plays a significant role in driving the perceptual impairment in EIB. Recent findings from the literature suggest that arousal has a very important role in biasing early cognitive functions. Hence, in the present study, we systematically investigate the role of valence (Experiment 1) and arousal (Experiment 2) in determining the impairment in EIB. The results suggest that when valence is controlled for, the stimuli with higher arousal level lead to greater impairment in target detection. Moreover, under high arousal condition, both positive and negative stimuli lead to significantly greater impairment in target detection. Present study suggests that impairment in EIB is sensitive to the arousal component of the emotional image as compared to valence. The arousal biased competition account that explains the effect of arousal on cognitive processing can sufficiently explains the current results.